« Travail noble, travail ingrat » : les ressorts d’une relation au travail ambivalente chez les nounous africaines à Paris - Adrien P. Batiga (Sociologies)
This article sets out to analyse the relationship that African nannies have with their work. These workers experience a double ambivalence. On the one hand, ambivalence in their relationship with their work, which they consider both noble and thankless, on the other, ambivalence in their status, given the conditions in which they carry out their work. We draw on data from an ethnographic survey (interviews and observations) conducted as part of our doctoral research with nannies and at the offices of the Syndicat national des auxiliaires parentales (SNAP).